2012
DOI: 10.1021/jm300318t
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Pyrrole Derivative 1-[5-(2-Fluorophenyl)-1-(pyridin-3-ylsulfonyl)-1H-pyrrol-3-yl]-N-methylmethanamine Fumarate (TAK-438) as a Potassium-Competitive Acid Blocker (P-CAB)

Abstract: In our pursuit of developing a novel and potent potassium-competitive acid blocker (P-CAB), we synthesized pyrrole derivatives focusing on compounds with low log D and high ligand-lipophilicity efficiency (LLE) values. Among the compounds synthesized, the compound 13e exhibited potent H(+),K(+)-ATPase inhibitory activity and potent gastric acid secretion inhibitory action in vivo. Its maximum efficacy was more potent and its duration of action was much longer than those of proton pump inhibitors (PPIs). Theref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 130 publications
(75 citation statements)
references
References 32 publications
1
70
0
1
Order By: Relevance
“…Peripheral or central hypersensitivity in viscera is a potentially unifying pathophysiological concept in functional heartburn and reflux hypersensitivity. In Japan, vonoprazan, a novel and potent first-in-class P-CAB, was launched 5,6 and now is expected to prove useful even in the treatment of functional esophageal disorders triggered by acid hypersensitivity. 7 Functional esophageal disorders include functional chest pain (A1), functional heartburn (A2), reflux hypersensitivity (A3), globus (A4), and functional dysphagia (A5) in the Rome IV edition.…”
Section: Functional Esophageal Disordersmentioning
confidence: 99%
See 2 more Smart Citations
“…Peripheral or central hypersensitivity in viscera is a potentially unifying pathophysiological concept in functional heartburn and reflux hypersensitivity. In Japan, vonoprazan, a novel and potent first-in-class P-CAB, was launched 5,6 and now is expected to prove useful even in the treatment of functional esophageal disorders triggered by acid hypersensitivity. 7 Functional esophageal disorders include functional chest pain (A1), functional heartburn (A2), reflux hypersensitivity (A3), globus (A4), and functional dysphagia (A5) in the Rome IV edition.…”
Section: Functional Esophageal Disordersmentioning
confidence: 99%
“…11 In the Rome IV section on FD, 5 only minor changes were introduced as compared to the previous Rome III criteria, 11 mainly to improve the specificity of the definition (Table). Among the major symptoms of FD, not only postprandial fullness, but also epigastric pain, epigastric burning, and early satiation should be "bothersome" symptoms.…”
Section: Functional Dyspepsiamentioning
confidence: 99%
See 1 more Smart Citation
“…Íåäàâíî ñèíòåçèðî-âàí åùå îäèí ïðåïàðàò äàííîãî ðÿäà -ïðîèçâîäíîå ïèððîëà ÒÀÊ-438, êîòîðûé îòëè÷àåòñÿ îò äðóãèõ Ð-CAB ìåäëåííîé ñêîðîñòüþ äèññîöèàöèè ñ ôåðìåí-òà.  èññëåäîâàíèÿõ íà aeèâîòíûõ ÒÀÊ-438 îêàçàë áî-ëåå ìîùíîå è äëèòåëüíîå àíòèñåêðåòîðíîå äåéñòâèå, ïî ñðàâíåíèþ ñ äðóãèìè Ð-CAB è ëàíñîïðàçîëîì [8].…”
Section: áëîêàòîðû Kunclassified
“…6) We identified two lipophilic cavities (LP-1 and LP-2 sites) and two polar residues (Tyr925 and Tyr928) in the enzyme that could be used to improve inhibitory activity. 7,8) Figure 1 displays the docking model of compound 1 and also the target LP-1, LP-2 sites and two Tyr residues. This model suggested that this compound binds to the enzyme mainly via the LP-1 site (mode A).…”
mentioning
confidence: 99%